Factors influencing colour variation and oxidative stability of South African game meat species - Neethling, Nikki Elrita (Stellenbosch : Stellenbosch University, 2016)
ENGLISH ABSTRACT: It is believed by many that the future of South African game farming depends on the development of a sustainable game meat industry. To develop such an industry, game meat products of consistently high quality must be supplied to consumers. To ensure the quality and consistency of these meat products, standard processing guidelines are required. No such guidelines are currently available and research on meat quality of South African game meat is thus required to establish these guidelines. There is currently only limited research available on the meat quality of game meat. Meat colour is important as it is the sole quality factor which consumers can use at the time of purchasing to select meat. Consumers prefer meat which is bright red in colour as they perceive it to be fresher, more wholesome and of higher quality than discoloured meat. Discoloured meat is often discounted, resulting in a loss of profits. Thus, maintaining the bright red colour of meat is essential in ensuring maximum profits. Colour stability is thus an important meat quality attribute which must be examined. Currently no research exists regarding the colour stability of South African game species. The colour stability of three major South African game species, blesbok (Damaliscus pygargus phillipsi), springbok (Antidorcas marsupialis) and fallow deer (Dama dama) were evaluated by measuring surface colour attributes (L*, a*, b*, hue, chroma and R (630/580)), surface myoglobin redox forms (percentage deoxymyoglobin, percentage oxymyoglobin and percentage metmyoglobin) and various biochemical attributes (pH, metmyoglobin reducing activity, oxygen consumption, thiobarbituric acid reactive substances, total, heme and non heme iron and total myoglobin) of three muscles, the infraspinatus (IS), longissimus thoracis et lumborum (LTL) and biceps femoris (BF) over an eight day colour stability trial at 2°C. The data indicated that the IS was the most colour stable of the three muscles for all the game species. For both the blesbok and fallow deer, the LTL was observed to be marginally more colour stable than the BF, whereas the LTL and BF for the springbok were observed to have similar colour stabilities. Overall the colour stability of the IS was determined to be eight days or more and that of the LTL and BF only one day for all three game species. Although significant gender differences were observed for the colour stability data, these were disregarded as no gender differences were visually perceived. Despite the similarities in colour stabilities noted for the muscles of the three game species, species differences were observed for various of the surface and biochemical attributes highlighting the need for both muscle and species specific processing strategies to improve colour stability of game meat. This study provided baseline data for the colour stability of game meat, specifically springbok, blesbok and fallow deer. It also highlighted the vast amount of research that is still required to ensure that the colour stability of game meat is optimised to ensure maximum colour stability.